Investigation on PEM water electrolysis cell design and components for a HyCon solar hydrogen generator. (11th May 2017) - Fallisch, Arne; Schellhase, Leon; Fresko, Jan; Zechmeister, Martin; Zedda, Mario; Ohlmann, Jens; Zielke, Lukas; Paust, Nils; Smolinka, Tom
Abstract: Hydrogen as a secondary energy carrier promises a large potential as a long term storage for fluctuating renewable energies. In this sense a highly efficient solar hydrogen generation is of great interest especially in southern countries having high solar irradiation. The patented Hydrogen Concentrator (HyCon) concept yields high efficiencies combining multi-junction solar cells with proton exchange (PEM) membrane water electrolysis. In this work, a special PEM electrolysis cell for the HyCon concept was developed and investigated. It is shown that the purpose-made PEM cell shows a high performance using a titanium hybrid fiber sinter function both as a porous transport layer and flow field. The electrolysis cell shows a high performance with 1.83 V at 1 A/cm 2 and 24 °C working under natural convection with a commercially available catalyst coated membrane. A theoretical examination predicts a total efficiency for the HyCon module from sunlight to hydrogen of approximately 19.5% according to the higher heating value. Highlights: Special designed PEM electrolysis cell with no fluidical bypass. Porous transport layer with high performance. PEM electrolysis working under natural convection at 1 A/cm 2 with 1.83 V at 24 °C. Predicted efficiency from sunlight to hydrogen above 19%.